Estudo da resistência à tração de cápsulas e troqueis metálicos cimentados, em função de alívio e retenção para o cimento - Pavanelli, Carlos Augusto [UNESP] (2002)
The objective of this study was to verify tensile strength of metallic capsules and dies, in stainless steel, cemented with zinc phosphate cement, representative of crowns and full crowns preparations. One hundred and forty four dies and respective capsules were made in Lathe CNC (Computer Numeric Control). The dimensions of the dies were: 9mm of diameter ín the base (gingival); 8mm of height; cervical line in shoulder with one millimeter of width and 135 degrees of inclination; and tapered of 10 degrees. The capsules were excavated in the interior of other cylinders, with the tapered form, identical and negative in relation to the form of the dies. Forty-eight experimental conditions, in three rejoinders each, were made. The changeable were: internal relief in the capsules; and horizontal sulcus in the capsules and the dies. The relief varied between 2µm (in the condition without relief), 30µm and 60µm (in the conditions with relief). The sulcus varied between no sulcus and three sulcus, as much in the capsules as in the dies, with 200 µm depth, in equal amounts of specimens for each condition of sulcus. The capsules and dies were cemented. The experimental conditions were not repeated, except in the rejoinders. The specimens were submitted to traction test in universal test machine of Emic (ltaquaquecetuba-SP) in the Department of Materials and Technology of the College of Engineering of Guaratinguetá, UNESP. The data were submitted to statistic analysis for methods ANOVA and Tukey, showing significant dífference for the variable relief and sulcus in the capsules, and interacting individually and among then. They had not presented difference statistics for changeable the sulcus in the dies. The tensile strength increased with the relief and the amount of sulcus in the capsules, but it remained in the same level with the sulcus in the dies